DEL. REV. STAT tit. 10, ch. 73, § 27 (1852). - (:unkn) unknown (General Publisher, 1852)
to provide for the weighing of hay, and for the measuring, or weighing, of coal, lime, grain, or any other matter sold in the said city; to regulate the storage of gunpowder, or any other dangerously combustible matter.
--
Keywords: GUN POWDER STORAGE